European Molecular Imaging Meeting 2020: Be Invited to Thessaloniki, Greece. - Zacharakis, Giannis (Molecular Imaging & Biology, 2020)
Molecular imaging has been at the forefront of these advancements, driving imaging science forward, challenging current thinking and creating the appropriate ecosystem for new technologies to be assessed, further developed and optimized before translation to clinical practice. The Main Abstract Categories for 2020 are as follows: Oncology Imaging; Neuroimaging; Cardiovascular Imaging; Immunology & Inflammation; Intra-Operative Imaging; Imaging Metabolism; Probe Chemistry; Imaging Technologies; Data Processing & Quantification, representing a full overview of the Molecular Imaging field.